Clinical Case of Using Cryopreserved Spermatozoa Obtained by Biopsy in Patients with Azoospermia - Podufaliy, Viktoriya V. (Problems of Cryobiology and Cryomedicine, 2013)
Previously developed highly effective method for cryopreservation of normozoospermic ejaculate was applied for single epididymal spermatozoa for following using in assisted reproductive technologies (ART). The cells were cooled in microcapillaries with solution of 20% sucrose and 15% glycerol from 22 down to –35°C with rate of 1 deg/min, from –35 down to –70°C with rate of 20 deg/min and thereafter plunged into liquid nitrogen. Post-thaw survival of spermatozoa was 92%. Oocytes were fertilized by injection of single spermatozoa, the embryos were cultured, assessed for pronuclei peresence and transfered into uterus. Pregnancy rate after using cryopreserved cells was higher (53.1%) than after using fresh asperated cells (46.1%). Thus the utilized method of cryopreservation could be effectively used in ART for patients with azoospermy. Probl Cryobiol Cryomed 2013; 23(3):260–266.